Level of knowledge of bioethics in odontological careers in two latin american universities - Buendía-López, Ana Laura; Álvarez de la Cadena-Sandoval, Carolina (Acta Bioethica, 2006)
A study was conducted simultaneously in two universities that teach odontology, in Chile and Mexico respectively, with the purpose of determining the level of knowledge that which students in this discipline possess. It was confirmed that in both universities, the level of knowledge is vague; however, in Chile, students have received more information or have obtained it themselves, although they have less resources at their disposal to increase their knowledge of bioethics. Generally speaking, in both universities, students do not possess a sufficient or, at the very least, acceptable knowledge about bioethics.